2009
DOI: 10.1093/brain/awp050
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral widespread mechanical pain sensitivity in carpal tunnel syndrome: evidence of central processing in unilateral neuropathy

Abstract: The aim of this study was to investigate whether bilateral widespread pressure hypersensitivity exists in patients with unilateral carpal tunnel syndrome. A total of 20 females with carpal tunnel syndrome (aged 22-60 years), and 20 healthy matched females (aged 21-60 years old) were recruited. Pressure pain thresholds were assessed bilaterally over median, ulnar, and radial nerve trunks, the C5-C6 zygapophyseal joint, the carpal tunnel and the tibialis anterior muscle in a blinded design. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
7
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 54 publications
11
126
7
2
Order By: Relevance
“…In fact, previous studies have also demonstrated that individuals with either CTS or LE also have lower PPT over the tibialis anterior muscle, supporting a central sensitization process in these pain conditions. 23,28 The results from the current study are clinically relevant, as they demonstrate that a musculoskeletal pain condition such as LE exhibits similar nerve sensitization as a neuropathic pain condition like CTS. A novel finding in the current study was that, generally, pressure nerve hypersensitivity was different between patients with CTS versus LE and was related to specific nerve trunks.…”
Section: Nerve Pressure Pain Hypersensitivity and Clinical Featuresmentioning
confidence: 66%
See 3 more Smart Citations
“…In fact, previous studies have also demonstrated that individuals with either CTS or LE also have lower PPT over the tibialis anterior muscle, supporting a central sensitization process in these pain conditions. 23,28 The results from the current study are clinically relevant, as they demonstrate that a musculoskeletal pain condition such as LE exhibits similar nerve sensitization as a neuropathic pain condition like CTS. A novel finding in the current study was that, generally, pressure nerve hypersensitivity was different between patients with CTS versus LE and was related to specific nerve trunks.…”
Section: Nerve Pressure Pain Hypersensitivity and Clinical Featuresmentioning
confidence: 66%
“…[ research report ] of previous studies conducted on individuals with LE or CTS. 23,28 However, PPT assessment in other areas unrelated to specific nerve trunks would have been helpful to clarify if current findings are neural tissue specific or just indicative of general hypersensitivity throughout the arm. In fact, previous studies have also demonstrated that individuals with either CTS or LE also have lower PPT over the tibialis anterior muscle, supporting a central sensitization process in these pain conditions.…”
Section: Nerve Pressure Pain Hypersensitivity and Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…This calculation generated a sample size of 16 individuals per group. This sample size calculation has been used in previous studies conducted in other pain disorders [13][14][15][16].…”
Section: Sample Size Determinationmentioning
confidence: 99%